2017
DOI: 10.2147/jaa.s142874
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of hypothalamo–pituitary–adrenal axis suppression during treatment with inhaled corticosteroids for childhood asthma

Abstract: ObjectiveTo describe recovery of adrenal insufficiency in asthmatic children treated with inhaled corticosteroids (ICS) and cortisol replacement therapy.DesignRetrospective, observational study.PatientsA total of 113 patients, 74 male; age 10.4 (3.3–16.5) years; beclomethasone-equivalent ICS dose, 800 μg, (100–1,000), tested by low dose short Synacthen (tetracosactide) test (LDSST), were studied. Test results were classified by basal and peak cortisol concentration: “normal” (basal >100 nmol/L, peak >500 nmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Oral or high doses of inhaled corticosteroids block the release of CRH and ACTH and then lower cortisol level. This Insufficiency continued even after treatment cessation for more than one year, with no significant difference between non steroid treated patients and the control subjects, while the results were within the reference range [32].…”
Section: (Mmol/l)mentioning
confidence: 64%
“…Oral or high doses of inhaled corticosteroids block the release of CRH and ACTH and then lower cortisol level. This Insufficiency continued even after treatment cessation for more than one year, with no significant difference between non steroid treated patients and the control subjects, while the results were within the reference range [32].…”
Section: (Mmol/l)mentioning
confidence: 64%
“…The pituitary–ovarian axis (HPO axis) interacts at multiple points. In recent years, with the deepening of research, the mechanism of the influence of stress on ovarian function in the hypothalamus, pituitary, and especially ovarian levels has been further revealed (Gangadharan et al, ; Gupta & Morley, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that women with excessively high sensory pressure have decreased levels of LH, elevated levels of FSH, decreased serum E2, and progesterone levels and increased ovulation cycle (Kudielka, Hellhammer & Wüst, 2009) interacts at multiple points. In recent years, with the deepening of research, the mechanism of the influence of stress on ovarian function in the hypothalamus, pituitary, and especially ovarian levels has been further revealed (Gangadharan et al, 2017;Gupta & Morley, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[26] Even when ICS doses are not reduced, HPAS seems to resolve in some patients. [27] This may be due to poor adherence to therapy or an increase in airway diameter with age, resulting in better control with reduced ICS doses.…”
Section: Management Of Hpasmentioning
confidence: 99%